Penerapan Metode Pembelajaran Doll Speak untuk Meningkatkan Aktivitas Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam di Kelas IV Sekolah Dasar Muhammadiyah 2 Kecamatan Sukajadi Pekanbaru. - Rani Magdalena; Rian Vebrianto (Instructional Development Journal, 2021)
This research aimed at knowing the increase of student learning activity on Natural Science subject through the implementation of Doll Speak learning activity method at the fourth grade of Elementary School of Muhammadiyah 2 Sukajadi District, Pekanbaru.  It was instigated by the low of student learning activity in the learning such as: students did not pay attention to the material explained by teachers, they did not want to question and answer teacher questions, they played when the teacher was explaining. It was a Classroom Action Research.  The subjects of this research were the teachers and students, and the objects were the Doll Speak learning method and student learning activity.  Observation, interview, and documentation were the techniques of collecting the data.  Descriptive statistic was the technique of analyzing the data.  Based on the research findings and data analyses, the implementation of Doll Speak learning method could increase student learning activity.  It could be identified that the mean percentage was 41.67% before the action.  After implementing the learning method in the first cycle, it was 60.32%.  In the second cycle, it increased to 80.16%.  Thus,Doll Speak learning method could increasestudent learning activity on Natural Science subject at the fourth grade of Elementary School of Muhammadiyah 2 Sukajadi District, Pekanbaru.